2010
DOI: 10.1111/j.1440-1681.2010.05426.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for suppression of spinal glial activation by dexmedetomidine in a rat model of monoarthritis

Abstract: SUMMARY1. Spinal glial cells play a key role in developing and maintaining allodynia and hyperalgesia following tissue inflammation. Dexmedetomidine, a highly selective a 2 -adrenoceptor (a 2 -AR) agonist, has exhibited a significant analgesic effect in various rodent models of chronic pain. However, whether spinal glial activation is involved in the analgesic effect of dexmedetomidine remains unknown. The present study investigated whether spinal administration of dexmedetomidine could antagonize glial activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 70 publications
(162 reference statements)
2
29
0
Order By: Relevance
“…44,45 We show that a reduction in spinal norepinephrine results in long term increases in spinal glial activation following peripheral nerve injury, similar to previous studies in our lab that examined earlier time points. 27 Consistent with our findings, noradrenergic receptor agonists have been shown to inhibit glial activation in vivo in rodent neuropathic pain models 46,47 and in vitro in spinal microglia 48 and astrocyte cultures 49 . Enhanced glial activation after injury likely results from increased primary afferent release of stimulating factors ( e.g.…”
Section: Discussionsupporting
confidence: 87%
“…44,45 We show that a reduction in spinal norepinephrine results in long term increases in spinal glial activation following peripheral nerve injury, similar to previous studies in our lab that examined earlier time points. 27 Consistent with our findings, noradrenergic receptor agonists have been shown to inhibit glial activation in vivo in rodent neuropathic pain models 46,47 and in vitro in spinal microglia 48 and astrocyte cultures 49 . Enhanced glial activation after injury likely results from increased primary afferent release of stimulating factors ( e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Recent findings suggest that astrocytes, but not microglia, express a 2A -ARs (50). Furthermore, dexmedetomidine, a highly selective a 2 -AR agonist, inhibits the activation of spinal astrocytes and extracellular signal-regulated kinase (ERK) signaling, but not that of microglia, probably by activating a 2 -AR expressed on astrocytes, which suppresses inflammatory and neuropathic pain (50,51). Taken together, it is suggested that the increase in NA induced by tramadol or amitriptyline acts on astrocytic a 2 -ARs and inhibits the pSNL-induced activation of spinal astrocytes, which may contribute to the preventive effect on neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that a 2A -AR was diffusely distributed in the primary afferents and dorsal horn neurons [5]; thus, presynaptic and postsynaptic a 2A -AR expressions in the spinal dorsal horn might both upregulate in CCI rats and contribute to dexmedetomidine-induced antiallodynia.…”
mentioning
confidence: 99%